Ideologies in South Korean Folktales - Jeerakamol, Rujjanee; Intajamornrak, Chommanad (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2024)
This research aimed to study Ideologies in South Korean Folktales by using Critical Discourse Analysis (CDA) framework. The data were 36 folktales from folktales for children in the Textbook by Sangkyo Lee, who won IBBY Honor List Award in 2016. The result of the study showed that there are 7 ideologies in South Korean folktales. These ideologies are an ideology related to behavior, an ideology related to people’s roles and duties in South Korean society, an ideology related to families, an ideology related to seniority, an ideology related to politics, an ideology related to patriarchy and an ideology related to collectivism, respectively. The results of the study also show that folktales are a form of discourse that can convey ideologies. These ideologies have been reproduced and transmitted in South Korean society for a long time.